Archiving (for) the Future: Creating First-Year Experience Programs Digital Archives - Coleman, Tara L.; Eiselein, Gregory; Vaughan, Mariya (My University, 2017)
K-State First is often contacted by schools interested in creating a first-year experience program. Between outside requests and internal needs, we decided to establish an archive in Kansas State University's institutional repository. We store, preserve, and showcase our work creating and maintaining our program in this archive. This session will provide an overview of how FYE programs can create their own digital archives documenting their programs' histories and successes. We will share concrete examples of K-State's decisions, the process of creating our Digital FYE archive, and we will provide recommendations for programs wanting to create their own archives.
Citation: Coleman, T. L., Eiselein, G., Vaughan, M. (2017). Archiving (for) the Future: Creating First-Year Experience Programs Digital Archives. 36th Annual Conference on the First-Year Experience, Atlanta, GA.
Keywords: First-year experience program; Annual Conference on the First-Year Experience; Archiving